2019
DOI: 10.3390/ijerph16010100
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in the Prevalence and Correlates of Elder Abuse in a Community-Dwelling Older Population in Korea

Abstract: Background: We examined gender differences in the prevalence estimates and correlates of elder abuse in a community-dwelling older population in Korea. Methods: We analyzed responses from the Living Profiles of Older People Survey (LPOPS), which comprises a nationally representative sample of non-institutionalized Korean older adults living in the community. A total of 10,184 older persons (4179 men and 6005 women) were included in the analysis. Results: The overall rate of elder abuse was 9.9%, and emotional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
39
0
24

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(71 citation statements)
references
References 30 publications
8
39
0
24
Order By: Relevance
“…The results are consistent with previous studies which have suggested that the urban elderly are at higher risk of abuse [61]. In this study, the association between socioeconomic status and elder abuse is significant and negative, which is consistent with previous literature [18,52]. Studies have shown that socioeconomic status plays an important role in several ways which may prevent elder abuse [19].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The results are consistent with previous studies which have suggested that the urban elderly are at higher risk of abuse [61]. In this study, the association between socioeconomic status and elder abuse is significant and negative, which is consistent with previous literature [18,52]. Studies have shown that socioeconomic status plays an important role in several ways which may prevent elder abuse [19].…”
Section: Discussionsupporting
confidence: 93%
“…A study conducted in Tamil Nadu has pointed out a significant protective impact of the wealth index on elder abuse [15]. Another study conducted in South Korea has reflected similar results [52].…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…In a number of previous studies, bad family relationships were associated with general abuse . The state of family relationships has been identified as a risk factor that varies from culture to culture . In Turkey, older individuals may have to live with their daughters/sons‐in‐law.…”
Section: Discussionmentioning
confidence: 99%
“…Using the Elderly Abuse in the Household it was found that about 35% of elderly were suffering from abuse and as expected the anxiety scores were higher in abused elderly as compared to the non-abused elderly. Evidence suggests that abuse of the elderly is one of the major causes of physical injury, illness, loss of efficiency, isolation [54], helplessness, sin, fear, embarrassment, post traumatic syndrome [55], anxiety, mental stress [56], despair, hopelessness, decrease Satisfaction with life, health and safety [57, 58], loss of property and also a threat to the survival and quality of life of the victims [54, 59].…”
Section: Discussionmentioning
confidence: 99%